Solucao de sistemas lineares com matrizes e vetores esparsos em computadores vetoriais - Ruiz Basso, Alessandro [UNESP]; Minussi, Carlos R. [UNESP]; Padilha, Antonio [UNESP] (My University, 1997)
This paper presents a methodology for solving a set of linear sparse equations on vector computers. The new methodology is able to exploit the matrix and vector sparsities. The implementation was made on a CRAY Y-MP 2E/232 computer and the results were taken from electric power systems with 118, 320, 725 and 1729 buses. The proposed methodology was compared with three previous methods and the results show the superior performance of the new one.
Keywords: Computer simulation; Electric power systems; Vectors; Linear space equations; Vector computers; Multiprocessing systems